Information security management in ITE centers of development (COD) and centers of excellence (COE) higher education institutions : basis for information security plan - Ignacio, Efren Yumang (San Carlos City, Pangasinan : [s.n.], 2015)
Traditionally, Higher Education Institutions in the Philippines have been very slow to respond to information security issues because of limited resources. The study explored into the extent of implementation of information security management for Centers of Development (CODs) and Centers of Excellence (COEs) higher education institutions (HEIs) offering Information Technology Education (ITE) programs in the country. The descriptive method of research was employed in this study using a survey instrument development by the researchers as a data gathering tool. In general, the study discovered that majority of the respondents were from private non-secretarial universities and colleges identified by the CHED as Centers of Development (CODs) and Centers of Excellence (COEs). Almost all CODs and COEs were offering Information Technology Education (ITE) Programs such as BSCS, BSIT and BSIS in the undergraduate program, MIT and DIT in the graduate program. Likewise, most of the respondents were employing more or less a thousand employees with an annual budget of relatively one hundred million pesos. The study revealed that CODs and COEs HEIs in the country were highly dependent on information technology and systems. The extent of implementation of Information security management in five areas was moderately implemented with a descriptive equivalent of close to completion. The study further discloses that the area of risk assessment and two sub-areas of process namely security technology strategy and policy development and enforcement were the least implemented among the five areas stated above. The study divulge that there is a significant correlation at 0.05 level between the profile and the extent of implementation of Information Security Management of ITE CODs and COEs. Notably, the programs offered on both CODs and COEs HEIs have no significant correlations with the extent of implementation of Information Security Management be integrated in the Commission on Higher Education Policies, Standards and Guidelines (PSG) for Information Technology Education programs. An information security plan was recommended to understand where to apply available resources to mitigate risk in a cost understand where to apply available resources to mitigate risk in a cost effective and efficient manner. It was further recommended to future researchers to include not only the identified CODs and COEs but also the HEIs that offer ITE programs accredited by the Philippine Accrediting Agencies.
Bibliography: pages 179-184.
CHED-La Union
Keywords: Information networks